Political Regimes, Contentious National Identity Question, and Nation-Building in African Countries: The Kenyan Case (1963 – 2020) - MASUMBE, Peter SAKWE (Advances in Social Sciences Research Journal, 2020)
Kenya’s successive political regimes’ contentiousness, like elsewhere in Africa, breeds the dearth of national identity, notwithstanding national identity’s relevance in characterising countries’ politico-economic and socio-cultural landscapes. National identity accelerates nation-building, hence, its inevitability for African countries; given their irrefutable need for statehoods. Arguably, the dearth of national identity constructs gratuitous upheavals as illustrated by post-election violence and contestations, in Kenya 2007, Ivory Coast 2010-2011, Cameroon 2018-2019, Nigeria 2018, Guinea Bissau 2020, etcetera. While seeking to divulge how Kenya’s national identity could emerge with its 4th President in 2017; this paper argues that, in African countries, the dearth of national identities propels political and economic failures, destroys citizens’ senses of belonging, undermines nation-building and enhances national disunity. Irked by these peccadilloes, fashioned by African leaders’ self-centredness; this work grounds on the elite theory to conclude that, leaders of African political regimes generate national identities’ dearth and their countries’ disunity and underdevelopment.